Soil and agricultural capability of UITM Sarawak, Samarahan campus farm / Hasmah Mohidin, Radziah Jack and Sulaiman Man - Mohidin, Hasmah; Jack, Radziah; Man, Sulaiman (2007)
Three major soil groups, three soil families and six soil series were identified in UiTM Sarawak, Samarahan campus farm. The three soil major groups are Red Yellow Podzolic (RYP), Gley and Organic. .The three soil families are BEKENU and MERIT Family of RYP Group, BIJAT and TATAU Family of Gley Group and ANDERSON Family of Organic group. The soil series identified are Bekenu of BEKENU Family, Merit and Jakar of MERIT Family, Daro of BIJAT Family, Tatau of TATAU Family and Gadong of ANDERSON Family.